2022
DOI: 10.1101/2022.01.29.22270095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CADM2is implicated in impulsive personality and numerous other traits by genome- and phenome-wide association studies in humans and mice

Abstract: Background: Impulsivity is a multidimensional heritable phenotype that broadly refers to the tendency to act prematurely and is associated with multiple forms of psychopathology. Methods: We performed genome-wide association studies (GWAS) of eight impulsive personality traits from the Barratt Impulsiveness Scale and the short UPPS-P Impulsive Personality Scale (N=123,509-133,517 23andMe research participants of European ancestry), and a measure of Drug Experimentation (N=130,684). Because these GWAS implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 131 publications
(297 reference statements)
0
7
0
Order By: Relevance
“…BALB/c mice have been suggested to be more ''impulsive'' than other inbred strains of mice (Otobe and Makino, 2004), but a direct assessment of impulsivity traits between the two substrains is yet to be explored. Impulsivity has been correlated with substance use disorders and eating disorders (Alcaraz-Iborra and Cubero, 2015;Kessler et al, 2016), particularly in the initiation of addiction behaviors, and has been demonstrated to have genetic components that have been identified in human GWAS (Dawe and Loxton, 2004;Bevilacqua and Goldman, 2013;Salatino-Oliveira et al, 2015;Giorgi et al, 2019;Sanchez-Roige et al, 2022). More specifically, treatment for attention deficit hyperactivity disorder (Lisdexamfetaminedimesylate; Vyvanse), which is stated to improve impulse control, has been shown to decrease binge-like eating (McElroy et al, 2015;Guerdjikova et al, 2016;Griffiths et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c mice have been suggested to be more ''impulsive'' than other inbred strains of mice (Otobe and Makino, 2004), but a direct assessment of impulsivity traits between the two substrains is yet to be explored. Impulsivity has been correlated with substance use disorders and eating disorders (Alcaraz-Iborra and Cubero, 2015;Kessler et al, 2016), particularly in the initiation of addiction behaviors, and has been demonstrated to have genetic components that have been identified in human GWAS (Dawe and Loxton, 2004;Bevilacqua and Goldman, 2013;Salatino-Oliveira et al, 2015;Giorgi et al, 2019;Sanchez-Roige et al, 2022). More specifically, treatment for attention deficit hyperactivity disorder (Lisdexamfetaminedimesylate; Vyvanse), which is stated to improve impulse control, has been shown to decrease binge-like eating (McElroy et al, 2015;Guerdjikova et al, 2016;Griffiths et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The current study is not without limitations. First, limited sample sizes likely hindered analyses of the (lack of) self-control and urgency traits, demonstrating the need for larger IPT GWAS (e.g., Becker et al, 2021;Sanchez-Roige et al, 2022). Second, and equally important, is the exclusion of non-European ancestry samples from the present study.…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
“…Intriguingly, in the context of this discussion, genes found in the most restrictively defined lists of deserts of introgression in modern human genomes (regions of the genome depleted of introgressed alleles from neanderthals/denisovans) (Reher, 2021 ), such as CADM2 , have been linked to personality traits like risk-taking behavior, impulsivity, addiction (Pasman et al, 2022 ; Sanchez-Roige et al, 2022 ). (Similar signals have been associated with other genes in introgression deserts such as CADPS2 or FOXP2 Sanchez-Roige et al, 2022 ). Of note, the gene ( CADM2 ) is listed alongside glutamate receptor GRIK3 , among the top candidate genes with potential connections to behavior in domestication studies (Freedman et al, 2016 ).…”
Section: Signals From Comparative (Paleo)genomicsmentioning
confidence: 99%